2022
DOI: 10.3390/brainsci12081115
|View full text |Cite
|
Sign up to set email alerts
|

Gray Matter Abnormalities in Patients with Complex Regional Pain Syndrome: A Systematic Review and Meta-Analysis of Voxel-Based Morphometry Studies

Abstract: Current findings on brain structural alterations in complex regional pain syndrome (CRPS) are heterogenous and controversial. This study aimed to perform a systematic review and meta-analysis to explore the significant gray matter volume (GMV) abnormalities between patients with CRPS and healthy controls (HCs). A systematic search of the PubMed, Web of Science, and MEDLINE databases was performed, updated through 27 January 2022. A total of five studies (93 CRPS patients and 106 HCs) were included. Peak coordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
3
1
Order By: Relevance
“…A voxel-based morphometry meta-analysis performed by Ma et al [25], contrary to certain observations in previous studies, there was an increase in the gray matter volume (GMV) in the medial left superior frontal gyrus (SFGmedial) and left striatum but reduced GMV in the corpus callosum. The GMV changes in SFGmedial were inversely related to the disease duration.…”
Section: Studying Effects Of Crps On Emotional and Autonomic Regions ...contrasting
confidence: 63%
“…A voxel-based morphometry meta-analysis performed by Ma et al [25], contrary to certain observations in previous studies, there was an increase in the gray matter volume (GMV) in the medial left superior frontal gyrus (SFGmedial) and left striatum but reduced GMV in the corpus callosum. The GMV changes in SFGmedial were inversely related to the disease duration.…”
Section: Studying Effects Of Crps On Emotional and Autonomic Regions ...contrasting
confidence: 63%
“…Thalamus atrophy has been shown in various chronic pain conditions in prior investigations. Previous research studies have also shown that the thalamus anatomy was associated with neuropathic pain, and the level of atrophy was correlated with pain intensity in chronic pain patients (47)(48)(49)). An explanation for the atrophy of the gray matter in the thalamus could be the overactivation caused by excitotoxins and inflammatory agents (50-52).…”
Section: Brain Regionsmentioning
confidence: 88%
“…One common measure in this context is the thickness and/or volume of brain grey matter in different brain regions, which can be estimated using standard MRI analyses techniques. Most commonly, reduced thickness of grey matter in certain brain regions, such as frontal areas, anterior cingulate cortex, and the insula, has been described in chronic pain compared to healthy controls (Ma et al, 2022;Wang et al, 2022). However, the exact relationship of grey matter thickness/volume and the perception of pain and the development and maintenance of chronic pain remains unclear.…”
Section: Structural Magnetic Resonance Imaging Of the Brainmentioning
confidence: 99%